2001
DOI: 10.1007/s004210100482
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous arterial baroreflex control of the heart rate during head-down tilt in heat-stressed humans

Abstract: The purpose of this study was to elucidate the effect of raised body temperature per se during acute heat stress on the spontaneous arterial baroreflex control of heart rate (fc) in humans. To investigate whether unloading of cardiopulmonary baroreceptors during whole-body heating would alter the arterial baroreflex control of fc, we controlled loading of the cardiopulmonary baroreceptors by head-down tilt (HDT) at angles of 5 degrees, 10 degrees, 15 degrees, and 30 degrees during heat stress produced by hot-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Similar to that observed with carotid-cardiac baroreflex responsiveness, the outcome of this assessment depends on whether the evaluated variable was heart rate or R-R interval. When heart rate was analyzed, heat stress did not change baroreflex responsiveness (128,275), however when R-R interval was analyzed, heat stress decreased baroreflex responsiveness (128,272,276). A primary limitation of the sequencing technique is that the range of changes in arterial blood pressure can be relatively small, which can affect the calculation of baroreflex responsiveness and the range to which these results can be applied.…”
Section: Heat Stress and Human Baroreflex Responsivenessmentioning
confidence: 89%
See 2 more Smart Citations
“…Similar to that observed with carotid-cardiac baroreflex responsiveness, the outcome of this assessment depends on whether the evaluated variable was heart rate or R-R interval. When heart rate was analyzed, heat stress did not change baroreflex responsiveness (128,275), however when R-R interval was analyzed, heat stress decreased baroreflex responsiveness (128,272,276). A primary limitation of the sequencing technique is that the range of changes in arterial blood pressure can be relatively small, which can affect the calculation of baroreflex responsiveness and the range to which these results can be applied.…”
Section: Heat Stress and Human Baroreflex Responsivenessmentioning
confidence: 89%
“…These observations raise the possibility that integrated baroreflex responsiveness may be impaired by heat stress. A number of other techniques have been used to evaluate integrated baroreflex responsiveness (4446,48,272,275277), including pharmacological manipulations of blood pressure (e.g., modified oxford technique), hypotensive challenges induced by simulated hemorrhage (e.g., LBNP and head-up tilt), and mathematical evaluations of heart rate and neural responses to spontaneous changes blood pressure (i.e., both the transfer function gain analysis and the sequencing technique). Results from these differing techniques sometimes contradict each other which complicate interpretation, though an alternate interpretation is that each of these different techniques may highlight different aspects of the reflex arc.…”
Section: Heat Stress and Human Baroreflex Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the observed hysteresis in the immediate recovery period, several studies have demonstrated the preservation of baroreflex control of HR during heat stress (8,11,38,40,41). Interestingly, although vascular sympathetic nerve activity is increased during heat stress (12), heat-induced attenuation of postsynaptic vasoconstrictor responsiveness results in progressive and profound reductions in MAP (14) in rats (20,26,28) and humans (11,14,39,42).…”
Section: Discussionmentioning
confidence: 99%
“…In protocol 1, the left atrial diameter (LAD) (in mm), as an index of cardiopulmonary baroreceptor loading [22][23][24], was measured by two-dimensional and M-mode echocardiography (Logiq 400 pro, GE Yokogawa Medical Systems, Tokyo) with a 3.5 MHz transducer. The images were obtained from the fourth left intercostal space in the parasternal short axis view at the level of the aortic valve at the end of the ventricular systole.…”
Section: Subjectsmentioning
confidence: 99%